2009
DOI: 10.1200/jco.2008.18.7740
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Identical Sibling Compared With 8/8 Matched and Mismatched Unrelated Donor Bone Marrow Transplant for Chronic Phase Chronic Myeloid Leukemia

Abstract: A B S T R A C T PurposeTransplantation of hematopoietic stem cells from an unrelated donor (URD) is an option for many patients who do not have an HLA-identical sibling donor (MSD). Current criteria for the selection of URDs include consideration for HLA alleles determined by high resolution typing methods, with preference for allele-matched donors. However, the utility and outcome associated with transplants from URDs compared with those from MSDs remains undefined. Patients and MethodsWe examined clinical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 33 publications
5
68
2
Order By: Relevance
“…21 In a large CIBMTR study on patients with chronic myeloid leukemia no significant difference in overall survival was noted between patients transplanted with HLA class I or class II mismatched grafts. 22 With regards to HLA class II disparities, several studies indicated that HLA-DQB1 disparities are not associated with mortality. 5,11,20 Because of the high priority given to HLA-DRB1 matching and the strong DRB1-DQB1 linkage disequilibrium, studies are often underpowered to reveal the clinical relevance of DQB1 disparities.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 99%
“…21 In a large CIBMTR study on patients with chronic myeloid leukemia no significant difference in overall survival was noted between patients transplanted with HLA class I or class II mismatched grafts. 22 With regards to HLA class II disparities, several studies indicated that HLA-DQB1 disparities are not associated with mortality. 5,11,20 Because of the high priority given to HLA-DRB1 matching and the strong DRB1-DQB1 linkage disequilibrium, studies are often underpowered to reveal the clinical relevance of DQB1 disparities.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 99%
“…In acute or chronic leukemia, transplantation from an HLA-matched or one HLA allelemismatched unrelated donor is associated with 5-10 and 10-15% lower survival rates, respectively, when compared with transplantation from an HLA-matched sibling donor, despite high resolution HLA typing. 39,40 With respect to the source of unrelated stem cells, HLA-mismatched bone marrow or cord blood transplants have been shown to give similar outcome in adults with acute leukemia. 2 Furthermore, outcomes with cord blood transplantation have been reported to be similar to that of HLA-matched bone marrow by Rocha et al 3 but this was not confirmed by Laughlin et al 2 In patients with MDS, DFS appears to be similar to that achieved using other unrelated hematopoietic stem cell sources, but comparative studies are required to better determine the role of UCBT for this group of patients.…”
Section: P-valuementioning
confidence: 99%
“…[7][8][9][10][11] Only 30% of patients in need of allo-HSCT will have a suitable human leukocyte antigen (HLA)-matched family member, and in the remainder an unrelated donor (UD) may be sought. 12 Although studies on large homogeneous samples in standard-risk hematopoietic malignancy (that is, chronic myeloid leukemia) suggest inferior results for UD compared with sibling transplants, 13,14 disadvantages of UD have not emerged in the trials on RIC allo-HSCT in CLL performed to date. 9,[15][16][17][18][19] However, analyses on donor effects in CLL have been hampered by small patient numbers, and generally disregarded the potentially important impact of HLA class-I allele and HLA C mismatch.…”
Section: Introductionmentioning
confidence: 99%